Transformation of Indian automobile industry through inter-organization IT initiative : AutoDX (B) - Verma, Sanjay (SAGE Business Cases., 2018)
The case centres on the 2015 common data exchange, an initiative for all automobile manufactures in India to share data. Part B in the two part cases series goes through the three phases of implementing the common data exchange initiative: standardization of data, application development and implementation and marketing and systems integration. Finally the cases discusses problems encountered during implementation.